Strength distribution of soft clay surround lime-column - Agus Setyo Muntohar, Hung-Jiun Liao (Taylor and Francis Group, 2007)
This paper presents the investigation result of the application of lime-column (LC) technique on expansive soft clay. The research studied the strength distribution surround the installed lime-column in the radial and vertical direction from the center of column. In this research, the LC was designed as single column with 50 mm in diameter (D), and the depth was 4D (= 200 mm). The soil strength surrounds the LC is determined by unconfined compression strength (UCS) test and static cone penetration (CPT) test. The test results show that the LC contributes to enhance the soil strength in radial direction up to 4D from the center of LC. Higher strength occurs near the LC and decreases with the distance from the LC center. It was also observed that soil strength tends to increase with time. The CPT results also showed that the installation of LC affected the soil strength to a depth of 4xD beneath the bottom of LC. This research also confirms that after installation of LC the water content of soil decreased near the LC, but beyond the distance of 4D in radial direction the water content remained its original value.